1993
DOI: 10.1111/j.1528-1157.1993.tb02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Anticonvulsant Activity and Minimal Toxicity of Methyl 4‐[(p‐Chlorophenyl)amino]‐6‐Methyl‐2‐Oxo‐Cyclohex‐3‐En‐l‐Oate and Some Prototype Antiepileptic Drugs in Mice and Rats

Abstract: The anticonvulsant and toxic properties of methyl 4-[(p-chlorophenyl)amino]-6-methyl-2-oxocyclohex-3-en-1-oate (ADD 196022), were compared with those of phenytoin (PHT), carbamazepine (CBZ), and valproate (VPA). These compounds were evaluated in mice and rats using well-standardized anticonvulsant testing procedures. Results indicate that ADD 196022 is a very potent anticonvulsant in the maximal electroshock seizure (MES) model. The compound was effective in nontoxic doses after intraperitoneal (i.p.) administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Allosteric modulators of GABA A receptors such as benzodiazepines, neuroactive steroids, and barbiturates have been identified that are useful as anxiolytics, anticonvulsants, anesthetics, and sedative-hypnotics. Previous in vivo studies reported that enaminones show potent anticonvulsion effects in chemical-induced epilepsy animal models but fewer side effects such as sedation, drowsiness, and dizziness (Mulzac and Scott, 1993;Eddington et al, 2003). Based on these in vivo results and our results, we hypothesized and confirmed that KRS-5Me-4-OCF 3 binds to benzodiazepine sites to exert its pharmaceutical actions.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Allosteric modulators of GABA A receptors such as benzodiazepines, neuroactive steroids, and barbiturates have been identified that are useful as anxiolytics, anticonvulsants, anesthetics, and sedative-hypnotics. Previous in vivo studies reported that enaminones show potent anticonvulsion effects in chemical-induced epilepsy animal models but fewer side effects such as sedation, drowsiness, and dizziness (Mulzac and Scott, 1993;Eddington et al, 2003). Based on these in vivo results and our results, we hypothesized and confirmed that KRS-5Me-4-OCF 3 binds to benzodiazepine sites to exert its pharmaceutical actions.…”
Section: Discussionsupporting
confidence: 76%
“…Previous in vivo studies reported that enaminones show potent anticonvulsion effects in chemical-induced epilepsy animal models but fewer side effects such as sedation, drowsiness, and dizziness (Mulzac and Scott, 1993;Eddington et al, 2003). Based on these in vivo results and our in vitro results, we hypothesized that KRS-5Me-4-OCF 3 might bind to ben- …”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…The compounds were found to be effective for the treatment of generalized tonic-clonic and complex partial seizures in experimental animals comprising rats and mice [3][4][5]. More recently, enaminones, particularly E121, have also been shown to exert an antiinflammatory effect in a murine model of inflammation [6].…”
Section: Introductionmentioning
confidence: 97%